Efficacy of Group Motivational Interviewing plus Brief Cognitive Behavior Therapy for relapse in amphetamine users with Co-occurring psychological problems at southern psychiatric hospital in Thailand - K. Sinsak Suvanchot (2018)
Objective: To evaluate the efficacy of a Group Motivational Interviewing plus Brief Cognitive Behavior Therapy (GMI-BCBT) in reducing amphetamine dependency in drug abused patients with recurring psychological problems. Material and Method: A quasi-experimental study was used with 200 patients from two psychiatric hospitals forming two groups of participants. The patients reported amphetamine use at least once in the past month prior to the present study. They were all assessed at baseline with three follow-up sessions. Patients in one psychiatric hospital were assigned to usual care and were the study group (n = 100) and patients at the other psychiatric hospital, the intervention group, were assigned to four sessions of GMI-BCBT plus usual care (n = 100). Regarding the follow-up outcomes, comparison of GMI-BCBT plus usual care and usual care only was analyzed by survival analysis since stopping amphetamine use. Results: Most (59.5%) patients suffered from major depression. The intervention group had significantly more survival rate within three months (p-value < 0.001). Both groups had a similar pattern of drug use in quantity and frequency. Their mean score of anxiety and depression were also reducing at baseline, three, and seven months (p-value < 0.001). Conclusion: The present result suggested that the combined therapy GMI-BCBT is more effectively reduced the rate of amphetamine use for out-patient at psychiatric hospital than usual care only.